Analisis Self-Efficacy Mahasiswa Departemen Ilmu Agama Islam Angkatan 2023 Universitas Negeri Padang - Jumadil Solihin Abadi; M. Yemmardotillah (Lembaga Yasin AlSys, 2025)
Self-efficacy is a crucial psychological factor that influences student motivation, learning autonomy, and academic achievement. However, studies on the dynamics of self-efficacy within the context of Islamic religious education, particularly in non-religious higher education institutions remain limited. This study aims to analyze the self-efficacy levels of students in the Department of Islamic Religious Studies at Universitas Negeri Padang, class of 2023, and to identify the factors influencing it. A descriptive qualitative approach with a phenomenological method was employed. The participants consisted of 20 students selected through purposive sampling. Data were collected through in-depth interviews and analyzed using Creswell’s phenomenological analysis model. The findings reveal that students’ self-efficacy falls into two main categories: high and low. Students with high self-efficacy demonstrate effective time management, resilience in facing academic and social challenges, and the ability to utilize social support to boost self-confidence. Conversely, students with low self-efficacy tend to procrastinate, experience anxiety during presentations, and show limited participation in academic and social activities. The study identifies five dominant factors influencing self-efficacy: social support, academic experience, learning strategies, psychological condition, and educational background. The study concludes that student self-efficacy is influenced not only by cognitive aspects but also by social, emotional, and religious factors. The implications highlight the importance of strengthening student self-efficacy holistically through lecturer engagement, academic mentoring programs, and campus-based religious activities.